Surface purification treatment method for cast / spray-formed metal part
Through two-stage baking and hydrogen-containing plasma etching, the problem of difficult removal of organic pollutants in small-size blind hole defects on the surface of precision casting and jet-formed metal parts is solved, and the thorough purification of the surface of the metal parts and the high quality of vapor deposition is achieved.
Patent Information
- Application Number
- CN202411807510.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
There are small-size blind hole defects on the surface of precision casting and jet-formed metal parts that are difficult to remove, making it difficult to remove organic pollutants during subsequent processing, affecting the quality of vapor deposition treatment.
Two-stage baking treatment is adopted: the first stage slowly heats up and removes liquid phase water, the second stage is high-temperature carbonized organic matter, combined with hydrogen-containing plasma etching to remove the oxide layer, ensuring no gas release in the blind holes and no stains on the surface.
The organic pollutants in the blind holes are completely removed, the oxidation problems caused by high-temperature baking are avoided, the surface purification of metal parts is ensured, and the quality of subsequent vapor deposition and the service life of the workpiece are ensured.
Smart Images

Figure CN119640202A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal surface purification treatment technology, in particular to a surface purification treatment method for a cast / injection-formed metal part. Background Art
[0002] There are blind hole defects such as pores, pinholes, shrinkage, and looseness on the surface of precision cast metal parts and injection-formed metal parts. Although subsequent sandblasting, mechanical cutting, polishing and other processes can remove most of the above defects on these metal parts, those small-sized surface defects with great depth and even difficult to observe with the naked eye are still difficult to remove. In the subsequent mechanical processing process, organic matter pollution will also be introduced into these surface deep hole defects; including lubricating oil during cutting, coolant containing animal / plant oils, and particles of polishing wax, etc., which are immersed or fall into these defects. These organic pollutants are difficult to be treated by existing traditional treatment methods, such as immersion and ultrasonic cleaning, which have poor cleaning efficiency. Because the depth-to-diameter ratio of the hole is large, it is difficult for the ultrasonic effect of a single-frequency ultrasonic wave to play a role due to the influence of adsorption and encapsulation of gases in small-sized deep holes. Even if dual-frequency ultrasound + cleaning solvent is used, it is difficult to remove all organic pollutants in the defects. If a high vacuum suction method is used, it is still difficult to remove these organic pollutants after 4 to 6 hours of treatment. The presence of these organic pollutants has adverse effects on subsequent surface vapor deposition treatment: 1) affecting the pumping speed of the vacuum system; 2) releasing impurities, worsening the vapor deposition environment, and even causing damage to all products in the vacuum chamber. Summary of the invention
[0003] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a surface purification treatment method for cast / injection-formed metal parts, which can completely and thoroughly convert organic matter accumulated in blind hole defects such as pores, pinholes, shrinkage, looseness, etc. on the surface of the metal parts into inorganic solid carbon-rich substances, and no gas is released from the surface blind holes during vacuum vapor deposition; and the baking process avoids the risk of directly using high-temperature baking to evaporate the liquid water in the blind holes at a high speed, thereby eliminating the risk of organic solid phase substances being enriched on the surface around the holes, thereby ensuring that the purification process does not affect the surface state of the workpiece, and subsequent vapor deposition can be directly carried out.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] The present invention provides a surface purification treatment method for a cast / injection-formed metal part, comprising the following steps:
[0006] Step 1: Ultrasonic cleaning and drying of cast / injection-formed metal parts;
[0007] Step 2: performing a baking process under continuous vacuum conditions; the baking process comprises two consecutive stages;
[0008] The first stage: heating from room temperature to 120-150°C at a heating rate of 20-30°C / min, and keeping the temperature for 20-30 minutes to remove the liquid phase water in the blind hole of the metal part and the water molecules physically adsorbed on the hole wall;
[0009] The second stage: heating to 420-550℃ within 15-25 minutes and keeping the temperature for 60-100 minutes; the organic matter in the blind hole is completely carbonized into inorganic matter, the decomposition gas in the carbonization process is discharged, and the residual solid carbon matter is retained on the hole wall or the bottom of the hole;
[0010] Step 3: etching the metal part using hydrogen-containing plasma to remove the oxide layer on its surface;
[0011] Step 4: introducing nitrogen gas to cool the metal part.
[0012] Preferably, the continuous vacuuming in step 2 specifically comprises: pumping the vacuum degree of the vacuum furnace to below 0.1 Pa and maintaining it.
[0013] Preferably, in the second stage of step 2, the baking temperature is 480-520° C., and the holding time is 80-100 minutes.
[0014] Preferably, the step 3 of etching the metal part with hydrogen-containing plasma is specifically as follows:
[0015] A mixed gas of argon and hydrogen is introduced, the furnace wall of the vacuum furnace is used as the anode, the metal part is used as the cathode, the voltage is 500-700V, glow discharge is generated, the current is 1.0-3.0A, the vacuum furnace pressure is 5.0-133Pa, and the etching time is 10-20 minutes.
[0016] Preferably, the flow rate ratio of argon to hydrogen is 1.5-9.
[0017] More preferably, the flow rate ratio of argon gas to hydrogen gas is (2.5-7.5); the pressure of the vacuum furnace is 60-70 Pa; the voltage for generating glow discharge is 620-670 V; the current is 1.5-2.0 A; and the etching time is 15-18 minutes.
[0018] Preferably, the step 4 of introducing nitrogen to cool the metal part is specifically as follows:
[0019] Nitrogen is introduced to cool the metal part, so that the metal part is cooled to below 100° C. within 10 to 25 minutes.
[0020] Preferably, the pollutants contained in the blind hole of the metal part after the treatment in step 1 include liquid water, coolant containing animal / plant oils and fats, adhesive particles and polishing wax organic particles.
[0021] Preferably, the ultrasonic cleaning in step 1 is specifically:
[0022] The metal part is immersed in an ultrasonic cleaning system with a cleaning agent added thereto to completely remove pollutants on its outer surface.
[0023] The present invention also provides a method for preparing a vapor deposition coating on the surface of a cast / injection-formed metal part. After the surface of the metal part is treated by the surface purification treatment method of the cast / injection-formed metal part, the metal part directly enters a vacuum coating system in a dry state for vapor deposition.
[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0025] (1) The surface purification treatment method of cast / injection-formed metal parts of the present invention is treated in a vacuum environment to avoid oxidation contamination (yellowing) of the metal parts surface. A two-stage baking method is adopted. In the first stage, the liquid water in the blind hole and the water molecules physically adsorbed on the hole wall are slowly removed by evaporation, avoiding direct high-temperature baking to cause the liquid water in the blind hole to evaporate at a high speed and bring out organic solid phase substances to be enriched on the surface around the hole. The subsequent treatment process leaves carbonization marks on the surface, affecting the quality and appearance of the subsequent vapor deposition coating; in the second stage, the organic matter is completely carbonized into inorganic matter, and the decomposition gas in the carbonization process is discharged. The residual solid carbon matter remains on the hole wall or the bottom of the hole. These inorganic carbonized substances do not need to be removed and are allowed to remain in the blind hole; they no longer release impurities in the subsequent vapor deposition process to affect the coating quality and appearance, as well as the service life and performance of the workpiece.
[0026] (2) Considering that lipid organic substances usually contain oxygen-containing groups, and the surfaces of various objects in the vacuum chamber release and adsorb oxygen-containing substances, these oxygen-containing substances will cause slight oxidation of the surface of the component during high-temperature baking. When the degree of this oxidation is high, it will seriously affect the quality of the subsequent vapor-deposited coating (film) on the surface of the component. At present, a separate electrochemical solution immersion treatment is usually used to remove surface oxides. The surface purification treatment method of the cast / spray-formed metal parts of the present invention, after the baking is completed, a mixed gas of argon and hydrogen is introduced, the furnace wall is used as the anode, and the component is used as the cathode to generate hydrogen plasma, and high-energy hydrogen ions or highly active hydrogen molecules react with the surface metal oxides, thereby removing the oxide layer, and the reduced loose metal element is etched and peeled off from the surface under the bombardment of high-energy ions, thereby obtaining a purified surface.
[0027] (3) The surface purification treatment method of cast / injection-formed metal parts of the present invention ensures that the purification process does not affect the surface state of the workpiece. After the treatment, the surface size and roughness remain unchanged, and there is no residue such as oxides and carbon scale / stains on the surface. Subsequent vapor deposition can be directly carried out, and the prepared vapor deposition coating is complete; it has strong bonding strength with the metal parts, and after 90 minutes of strong ultrasound, there is no local peeling of the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of various stages in the blind hole of a metal part in step 2 of an embodiment of the present invention, wherein A is the initial state, B is the state after the first stage of baking, and C is the state after the second stage of baking.
[0029] Figure 2 The present invention is a surface purification method according to an embodiment of the present invention. DETAILED DESCRIPTION
[0030] An embodiment of the present invention provides a surface purification method for a cast / injection-formed metal part, comprising the following steps:
[0031] Step 1: Ultrasonic cleaning and drying of the cast / injection-formed metal parts; this step purifies all visible organic pollutants on the outer surface except the blind hole positions, and avoids contamination of all visible positions of these outer surfaces by carbonized residues during subsequent processing.
[0032] Step 2: performing a baking process under continuous vacuum conditions; the baking process comprises two consecutive stages;
[0033] The first stage: heating from room temperature to 120-150°C at a heating rate of 20-30°C / min, and keeping the temperature for 20-30 minutes to remove the liquid phase water in the blind hole of the metal part and the water molecules physically adsorbed on the hole wall;
[0034] The second stage: heating to 420-550℃ within 15-25 minutes and keeping the temperature for 60-100 minutes; the organic matter in the blind hole is completely carbonized into inorganic matter, the decomposition gas in the carbonization process is discharged, and the residual solid carbon matter is retained on the hole wall or the bottom of the hole;
[0035] This step completely carbonizes and solidifies the organic matter remaining in the blind hole, and no cracking and outgassing will occur under the vacuum system conditions of the subsequent vapor deposition.
[0036] Step 3: Etch the metal part with hydrogen-containing plasma to remove the oxide layer on its surface; this step reduces the oxidation that may be generated on the visible outer surface during the above-mentioned high-temperature baking process and removes it by ion etching.
[0037] Step 4: introducing nitrogen gas to cool the metal part.
[0038] The cast / spray-formed metal parts in the embodiments of the present invention have pores, pinholes, shrinkage, looseness, sand holes, and more or less various defects on the surface, such as shrinkage, sand holes, pores, etc. These holes are all blind holes with a fine size (~1 to 1000 microns). Due to the subsequent processing (such as mechanical cutting, polishing, cleaning, etc.), there are multi-phase substances ( Figure 1 A): water (liquid phase); cutting coolant (liquid phase + solid phase (suspension), including cutting oil - various animal and plant lipids, etc.), bonding colloid particles and polishing wax particles (mixture containing organic substances, solid phase).
[0039] like Figure 1 As shown in B, the main purpose of the first stage of low-temperature vacuum baking is to slowly remove the liquid water in the blind hole and the water molecules physically adsorbed on the hole wall by evaporation. In this stage, the organic solid phase material is still in a stable state.
[0040] like Figure 1 As shown in C, the second stage of high-temperature vacuum baking completely carbonizes the organic matter into inorganic matter, the decomposition gas in the carbonization process is discharged, and the residual solid carbon matter remains on the hole wall or hole bottom. These inorganic carbonized substances do not need to be removed and are allowed to remain in the blind hole; they will no longer release impurities in the subsequent vapor deposition process to affect the coating quality and appearance, as well as the service life and performance of the workpiece.
[0041] In the embodiment of the present invention, when the cast / injection-formed metal parts obtain an ideal surface during the machining process, the coolant used is a mixed multiphase substance of animal and plant oils, additives and water. Wet sandblasting, polishing and other links may also bring liquid water. These mixed multiphase substances will inevitably penetrate / enter the residual surface pores, pinholes, shrinkage, looseness and other blind hole defects of the component. Their melting points, boiling points and carbonization temperatures are very different. For example, the boiling point (vaporization) temperature of water is 100°C, the carbonization temperature of double-sided adhesive organic matter and polishing wax is about 200-400°C, and the carbonization temperature of cutting fluid grease may reach 500-550°C. When high-temperature carbonization is implemented, low-boiling point substances are rapidly vaporized, such as water becomes water vapor, resulting in a sharp increase in pressure in the blind hole; some of the substances in the blind hole are ejected and adsorbed on the surface of the component, and they form stains / carbon scale on the surface of the component after surface reaction or carbonization. In order to fully carbonize the organic matter in the blind hole, the final baking temperature of the present invention reaches 450-550°C, so that all organic matter such as cutting fluid and grease in the blind hole can be completely carbonized (solidified). In order to prevent the rapid vaporization and eruption of low-melting-point liquid substances, the present invention maintains a sufficient time in the range of room temperature to about 150°C, allowing the liquid low-melting-point substances to evaporate slowly. During the entire baking stage, the component is in a high vacuum environment, which is conducive to the timely removal of volatilized and cracked gases in the blind hole. The technical measures of two-stage baking effectively ensure that the organic matter in the blind hole is completely carbonized and there is no stain / carbon scale on the surface of the component.
[0042] Lipid organic substances usually contain oxygen-containing groups, and the surfaces of various objects in the vacuum chamber release and adsorb oxygen-containing substances. These oxygen-containing substances will cause slight oxidation of the surface of the component during high-temperature baking. When the degree of this oxidation is high, it will seriously affect the quality of the subsequent vapor-deposited coating (film) on the surface of the component. At present, a separate electrochemical solution immersion treatment is usually used to remove surface oxides. The present invention cleverly uses a high-temperature vacuum environment to achieve hydrogen plasma surface etching or ion source etching to remove and clean the surface oxide layer. That is, after the baking is completed, a mixed gas of argon and hydrogen is introduced, and the furnace wall is used as the anode and the component is used as the cathode to generate hydrogen plasma. High-energy hydrogen ions or highly active hydrogen molecules react with surface metal oxides to remove the oxide layer. The reduced loose metal element is etched and peeled off from the surface under high-energy ion bombardment, thereby obtaining a purified surface.
[0043] The embodiments of the present invention reasonably and efficiently carbonize / solidify organic pollutants in micro-sized blind holes, and in the process minimize the contamination of the reaction products on the remaining surfaces of the component; hydrogen plasma is used to eliminate the adverse effects of possible oxidation on the remaining surfaces. In view of the organic pollutants that may appear in the blind holes, reasonable process parameters such as carbonization temperature and treatment time are formulated according to their carbonization characteristics. The pollutants in the blind holes are in a three-phase mixed state of solid, liquid and gas. The present invention accelerates the extraction of gaseous substances in the blind holes through vacuum; the liquid phase substances are vaporized and discharged by staged baking, which is effectively isolated from the solidification / carbonization of solid phase organic substances, avoiding the disadvantage of existing similar baking technologies that carbon-rich substances are deposited on the remaining surfaces of the components. Considering that although vacuum baking is used, the release of oxygen-containing substances in the vacuum environment may cause the remaining surfaces of the components to be slightly oxidized, the present invention uses high-temperature hydrogen-containing plasma to perform surface etching to completely remove them. The components treated by the present invention can be directly used for subsequent gas phase deposition without other supporting treatments. Further, the removal of oxides on the remaining surfaces of the components can be accelerated by replacing the hydrogen-containing plasma glow etching cleaning of the present invention with a special ion source. The invention can quickly, efficiently and thoroughly purify the contaminated metal components in the blind holes, laying a foundation for obtaining high-quality and high-bonding-strength vapor deposition coatings.
[0044] In the embodiments of the present invention, the changes in surface hardness of components before and after treatment are compared to characterize the influence of the treatment process on the mechanical properties of the substrate; the physical vapor (magnetron) deposition equipment and technology of Guangzhou Jintai Technology Co., Ltd. are used to prepare carbon films on the surfaces of components in various treatment states, and the component substrates and components coated with carbon films are visually inspected; and deionized water, strong ultrasound and other means are used to compare / evaluate the beneficial effects achieved by the present invention.
[0045] In the embodiment of the present invention, the vacuum equipment used is a commercially available Hauzer 850 system, and the high valve of the system is always closed. The surface immersion ultrasonic pre-cleaning uses a GT-Cleaning cleaning system, and a cleaning agent is added during the cleaning process.
[0046] The following examples are further described. However, the following examples are only for illustration and should not be construed as limiting the implementation of the present invention.
[0047] Example 1304 Surface treatment of austenitic stainless steel castings
[0048] The ingot was cut at the gate of the 304 austenitic stainless steel lost wax casting, and 30 samples of 30x30x10 mm were processed by turning with cutting fluid cooling, and then these test pieces were polished respectively with commercially available white and purple polishing waxes. After polishing, there are still pores and shrinkage holes visible to the naked eye on the upper and side surfaces, and surface pinholes can be observed under a 500x optical microscope. The inside of these pinholes is usually contaminated by cutting coolant, double-sided tape organic matter particles, and polishing wax organic particles. In order to better illustrate the effect of the present invention, these samples were placed in the commercially available JC-17 cutting fluid (Changzhou Jiachen Oil Products Co., Ltd.) for 48 hours in this example. These samples were processed according to Figure 2 The surface treatment is carried out according to the process shown and the inspection is as follows:
[0049] 1) Take out the test piece soaked in JC-17 cutting fluid and wipe the surface liquid stains with cotton yarn, use GT-Cleaning cleaning system to clean in the corresponding degreasing and dewaxing ultrasonic tank, and then blow dry with compressed air. After ultrasonic pre-cleaning, the appearance of the sample is clean, and there is no greasy residue when wiped with white gloves. Keep 10 samples and do not enter the subsequent process; 20 samples enter the subsequent process; and select one of the test pieces to mark it, and use microhardness test to test its hardness, and its hardness value is measured to be 313HV 100 .
[0050] 2) The cleaned sample is mounted on the workpiece rotating rack in the Hauzer 850 vacuum furnace, and the background vacuum is evacuated to below 0.1 Pa and maintained, and then the component is heated. First, it is heated to the initial stage temperature of 150°C at a heating rate of 30°C / min, and kept at 150°C for 20 minutes. Then, the vacuum chamber temperature is raised to 500°C within 20 minutes, and the heating power is turned off after being kept at this temperature for 90 minutes.
[0051] 3) A mixed gas with a flow rate ratio of Ar:H2=4 is introduced into the furnace body to make the vacuum chamber pressure reach 65 Pa. Then the connected DC power supply voltage reaches 650V, a stable glow discharge is generated in the furnace body, and the current reaches 1.8A. After etching and cleaning the workpiece surface for 15 minutes, the mixed gas and power supply are turned off.
[0052] 4) Turn off all the vacuum pumps in the vacuum system and pump in high-purity liquid nitrogen (purity better than 99.9%) to make the pressure in the furnace reach 1.05 atmospheres (greater than 1 atmosphere to prevent ambient gas from entering) within 2 minutes. The exhaust device of the furnace door is opened to quickly take away the heat. After 10 minutes of pumping in liquid nitrogen, the temperature in the furnace is reduced to 70°C.
[0053] The sample marked in step 1) was taken out for observation and testing. The surface was brightly polished, with no residual material on the surface and no abnormal changes in the pores / shrinkage. There was no residue near the pinhole surface under a 500x optical microscope. The surface hardness was measured to be 312V 100 , indicating that the above surface treatment process has basically no effect on the mechanical properties of metal parts.
[0054] After the above 30 samples were placed in the physical vapor (magnetron) deposition system of Guangzhou Jintai Technology Co., Ltd. to prepare black carbon-based coatings, it was found that: 1) 20 samples that had completely undergone the processing steps of the present invention had complete surface coatings; after 60 minutes of ultrasound (strong ultrasound) in an ultrasonic tank with a capacity of 60kHz, 1.5kW, and a deionized water volume of 20L, the surface coating was still intact, and there was no local peeling on the surface. 2) Only 10 samples that had undergone step 1 were retained, of which 2 had local peeling after the coating was completed; after the ultrasonic treatment with the above parameters, white spots of varying densities (local peeling) appeared on the surface of all coatings. It can be seen that the present invention not only effectively improves the appearance quality of the coating, but also especially improves the film-base bonding strength through reasonable carbonization / solidification treatment of organic matter in the blind hole.
[0055] Example 2 Surface treatment of titanium alloy TC4 casting
[0056] The ingot was cut from the gate of the TC4 titanium alloy lost wax casting, and 20 samples of 30x30x10 mm were machined by turning with cutting fluid cooling, and then the test pieces were polished with commercially available white and purple polishing waxes. After polishing, there were still pores and shrinkage holes visible to the naked eye on the upper and side surfaces; surface pinholes could be observed under a 500x optical microscope, and the inside of these pinholes were usually contaminated by cutting coolant, double-sided adhesive organic matter particles, and polishing wax organic particles. In order to better illustrate the effect of the present invention, the surface of the test piece was pasted / torn off with 3M double-sided tape 20 times, and then the samples were placed in the commercially available JC-17 cutting fluid (Changzhou Jiachen Oil Products Co., Ltd.) for 8 hours. These samples were cut according to Figure 2 The surface treatment is carried out according to the process shown and the inspection is as follows:
[0057] 1) Take out the test piece soaked in JC-17 cutting fluid and wipe the surface liquid stains with cotton yarn, use GT-Cleaning cleaning system to clean in the corresponding degreasing, dewaxing and degumming ultrasonic tank, and then blow dry with compressed air. After ultrasonic pre-cleaning, the appearance of the sample is clean, and there is no greasy residue when wiped with white gloves. Keep 10 samples and do not enter the subsequent process; 10 samples enter the subsequent process; and select one of the test pieces to mark it, and test its hardness with a microhardness tester, and its hardness value is measured to be 386HV 100 .
[0058] 2) The cleaned sample is mounted on the workpiece rotating rack in the Hauzer 850 vacuum furnace, and the background vacuum is evacuated to below 0.1 Pa and maintained, and then the component is heated. First, the temperature is heated to the initial stage temperature of 120°C at a heating rate of 20°C / min, and kept at 120°C for 30 minutes. Then, the vacuum chamber temperature is raised to 550°C within 25 minutes, and the heating power is turned off after keeping at this temperature for 60 minutes.
[0059] 3) A mixed gas with a flow rate ratio of Ar:H2=9 is introduced into the furnace body to make the vacuum chamber pressure reach 133 Pa. Then the connected DC power supply voltage reaches 500V, a stable glow discharge is generated in the furnace body, and the current reaches 2.9A. After etching and cleaning the workpiece surface for 18 minutes, the mixed gas and power supply are turned off.
[0060] 4) Turn off all the vacuum pumps of the vacuum system and introduce high-purity nitrogen (purity better than 99.99%) at a flow rate of 2000sccm to make the pressure in the furnace reach 1.02 atmospheres in 4 minutes, and the exhaust device of the furnace door is pushed open; after continuing to introduce nitrogen at this flow rate for 25 minutes, the temperature in the furnace is reduced to 100°C.
[0061] The sample marked in step 1) was taken out for observation and testing. The surface was brightly polished, with no residual material on the surface and no abnormal changes in the pores / shrinkage. There was no residue near the pinhole surface under a 500x optical microscope. The surface hardness was measured to be 389V 100 , indicating that the above surface treatment process has basically no effect on the mechanical properties of metal parts.
[0062] After the above 20 samples were placed in the physical vapor (magnetron) deposition system of Guangzhou Jintai Technology Co., Ltd. to prepare black carbon-based coatings, it was found that: 1) 10 samples that had completely undergone the treatment steps of the present invention had intact surface coatings; after 60 minutes of strong ultrasound, there was no local peeling on the surface. 2) 10 samples that only underwent step 1, all samples were intact and had no local peeling after coating; but after 10 minutes of strong ultrasound, some samples had local peeling on the surface, and after 30 minutes, all samples had local peeling on the surface.
[0063] Example 3 Surface treatment of GH2036 casting
[0064] GH2036 alloy is an aging type iron-based high-temperature alloy. The casting is cast by lost wax casting. The ingot is cut at the gate of the casting, and 20 30x30x10 mm specimens are machined by turning with cutting fluid cooling and heat treated according to the national standard. Then, these specimens are polished with commercially available white and purple polishing waxes. After polishing, there are still pores and shrinkage holes visible to the naked eye on the upper and side surfaces; surface pinholes can be observed under a 500x optical microscope. The surface of the specimen is pasted / torn with 3M double-sided tape 20 times, and then these specimens are placed in the commercially available JC-17 cutting fluid (Changzhou Jiachen Oil Products Co., Ltd.) for 4 hours. These specimens are according to Figure 1 The surface treatment is carried out according to the process shown and the inspection is as follows:
[0065] 1) Take out the test piece soaked in JC-17 cutting fluid and wipe the surface liquid stains with cotton yarn, use GT-Cleaning cleaning system to clean in the corresponding degreasing, dewaxing and degumming ultrasonic tank, and then blow dry with compressed air. After ultrasonic pre-cleaning, the appearance of the sample is clean, and there is no greasy residue when wiped with white gloves. Keep 10 samples and do not enter the subsequent process; 10 samples enter the subsequent process; and select one of the test pieces to mark it, and use microhardness test to test its hardness, and its hardness value is measured to be 428HV 100 .
[0066] 2) The cleaned sample is mounted on the workpiece rotating rack in the Hauzer 850 vacuum furnace, and the background vacuum is evacuated to below 0.1 Pa and maintained, and then the component is heated. First, the temperature is heated to the initial stage temperature of 130°C at a heating rate of 25°C / min, and the temperature is kept at 130°C for 25 minutes. Then, the vacuum chamber temperature is raised to 420°C within 25 minutes, and the heating power is turned off after being kept at this temperature for 100 minutes.
[0067] 3) A mixed gas with a flow rate ratio of Ar:H2=4 is introduced into the furnace body to make the vacuum chamber pressure reach 5 Pa. Then the connected DC power supply voltage reaches 700V, a stable glow discharge is generated in the furnace body, and the current reaches 1.1A. After etching and cleaning the workpiece surface for 16 minutes, the mixed gas and power supply are turned off.
[0068] 4) Turn off all the vacuum pumps of the vacuum system and pump in high-purity liquid nitrogen (purity better than 99.9%) to make the pressure in the furnace reach 1.05 atmospheres within 2 minutes, and the exhaust device of the furnace door is opened; then continue to pump in liquid nitrogen for 15 minutes, and the temperature in the furnace is reduced to 70°C.
[0069] The sample marked in step 1) was taken out for observation and testing. The surface was brightly polished, with no residual material on the surface and no abnormal changes in the pores / shrinkage. There was no residue near the pinhole surface under a 500x optical microscope. The surface hardness was measured to be 430HV100 , indicating that the above surface treatment process has basically no effect on the mechanical properties of metal parts.
[0070] After the above 20 samples were placed in the physical vapor (magnetron) deposition system of Guangzhou Jintai Technology Co., Ltd. to prepare black carbon-based coatings, it was found that: 1) 10 samples that had undergone the treatment steps of the present invention had complete surface coatings; after 90 minutes of strong ultrasound, there was no local peeling on the surface. 2) 10 samples that had only undergone step 1, after the coating was completed, all samples were intact and had no local peeling; after 60 minutes of strong ultrasound, there was still no local peeling on the surface, and after 90 minutes, a small amount of local peeling appeared on the surface of all samples.
[0071] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for surface purification of cast / injection-formed metal parts, characterized in that: The following steps are involved: Step 1: Ultrasonic cleaning and drying of cast / injection-formed metal parts; Step 2: performing a baking process under continuous vacuum conditions; the baking process comprises two consecutive stages; The first stage: heating from room temperature to 120-150°C at a heating rate of 20-30°C / min, and keeping the temperature for 20-30 minutes to remove the liquid phase water in the blind hole of the metal part and the water molecules physically adsorbed on the hole wall; The second stage: heating to 420-550℃ within 15-25 minutes and keeping the temperature for 60-100 minutes; the organic matter in the blind hole is completely carbonized into inorganic matter, the decomposition gas in the carbonization process is discharged, and the residual solid carbon matter is retained on the hole wall or the bottom of the hole; Step 3: etching the metal part using hydrogen-containing plasma to remove the oxide layer on its surface; Step 4: Cool the metal part by introducing nitrogen gas.
2. The surface purification method of a cast / injection-formed metal part according to claim 1, characterized in that: The continuous vacuuming in step 2 specifically includes: evacuating the vacuum degree of the vacuum furnace to below 0.1 Pa and maintaining it.
3. The surface purification treatment method of a cast / injection-formed metal part according to claim 1, characterized in that: In the second stage of step 2, the baking temperature is 480-520° C. and the holding time is 80-100 minutes.
4. The surface purification method of a cast / injection-formed metal part according to claim 1, characterized in that: The step 3 of etching the metal part with hydrogen-containing plasma is specifically as follows: A mixed gas of argon and hydrogen is introduced, the furnace wall of the vacuum furnace is used as the anode, the metal part is used as the cathode, the voltage is 500-700V, glow discharge is generated, the current is 1.0-3.0A, the vacuum furnace pressure is 5.0-133Pa, and the etching time is 10-20 minutes.
5. The surface purification treatment method of a cast / injection-formed metal part according to claim 4, characterized in that: The flow rate ratio of the argon gas to the hydrogen gas is 1.5-9.
6. The surface purification method of a cast / injection-formed metal part according to claim 4, characterized in that: The flow rate ratio of argon gas to hydrogen gas is 2.5-7.5; the pressure of the vacuum furnace is 60-70 Pa; the voltage for generating glow discharge is 620-670 V; the current is 1.5-2.0 A; and the etching time is 15-18 minutes.
7. The surface purification method of a cast / injection-formed metal part according to claim 1, characterized in that: The step 4 of introducing nitrogen to cool the metal part is specifically as follows: Nitrogen is introduced to cool the metal part, so that the metal part is cooled to below 100° C. within 10 to 25 minutes.
8. The surface purification method of a cast / injection-formed metal part according to claim 1, characterized in that: The pollutants contained in the blind hole of the metal part after the treatment in step 1 include liquid water, coolant containing animal / plant oils and fats, adhesive particles and polishing wax organic particles.
9. The surface purification method of a cast / injection-formed metal part according to claim 1, characterized in that: The ultrasonic cleaning in step 1 is specifically: The metal part is immersed in an ultrasonic cleaning system with a cleaning agent added thereto to completely remove pollutants on its outer surface.
10. A method for preparing a vapor deposition coating on the surface of a cast / spray-formed metal part, characterized in that: After the surface of the metal part is treated by the surface purification treatment method for a cast / injection-formed metal part as claimed in any one of claims 1 to 9, the metal part directly enters a vacuum coating system in a dry state for vapor deposition.
Citation Information
Cited By
Table surface side wall passivation method for class-II superlattice infrared detector and infrared detector
CN121487382A